2021
DOI: 10.1186/s12871-021-01355-0
|View full text |Cite
|
Sign up to set email alerts
|

Labor epidural analgesia versus without labor epidural analgesia for multiparous women: a retrospective case control study

Abstract: Background Labor epidural analgesia (LEA) effectively relieves the labor pain, but it is still not available consistently for multiparous women in many institutions because of their obviously shortened labor length. Methods A total of 811 multiprous women were retrospective enrolled and firstly divided into two groups: LEA group or non-LEA group. And then they were divided into seven subgroups and analyzed according to the use of LEA and cervical d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 22 publications
(29 reference statements)
0
7
0
Order By: Relevance
“…Labor pain will elicit physiological stresses and perinatal complications [ 3 ]. Pregnant women choose cesarean delivery due to the fear of labor pain, which is one of the important influencing factors for the increasing rate of cesarean delivery in China [ 4 ]. Intraspinal nerve block anesthesia for labor analgesia features satisfactory nerve block and ideal analgesic effect, but the uncertainty of its effect on the labor process and the fetus has prevented its widespread implementation in China [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Labor pain will elicit physiological stresses and perinatal complications [ 3 ]. Pregnant women choose cesarean delivery due to the fear of labor pain, which is one of the important influencing factors for the increasing rate of cesarean delivery in China [ 4 ]. Intraspinal nerve block anesthesia for labor analgesia features satisfactory nerve block and ideal analgesic effect, but the uncertainty of its effect on the labor process and the fetus has prevented its widespread implementation in China [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Out of 38 women who had normal vaginal delivery, 1 participant (2.6%) had postpartum hemorrhage .p value(less than 0.05) is statistically significant In a study conducted by Shuzhi Luo et al, early administration of epidural analgesia increases postpartum blood loss. 41 There was no Blood transfusion reported in the study population, no puerperal complications reported as well and no death had occurred in the study participants.…”
Section: Complicationsmentioning
confidence: 77%
“…Hung T-H. et al [39] investigating this topic, noticed a significantly higher percentage of newborn babies < 7 points in 1 minute of life in primigravida who were administered epidural analgesia. Luo S. et al [43] found that the use of epidural anesthesia during cervical dilatation of 2 cm or > 4 cm significantly reduces the Apgar score, while at the stage of 3 cm of cervical dilatation they did not find any differences.…”
Section: Discussionmentioning
confidence: 96%
“…Luo S. et al [43] deepened this analysis and found that the use of epidural anesthesia can significantly increase blood loss in women with 2 and 3 cm cervical dilatation. They did not show significant differences in women with dilatation of 4 cm or more [43].…”
Section: Discussionmentioning
confidence: 99%